Multiple Fano resonance excitation of all-dielectric nanoholes cuboid arrays in near infrared region - Yu, Shilin; Li, Hao; Wang, Yusen; Gao, Ziang; Zhao, Tonggang; Yu, Jianguo (Results in physics, 2021)
•An all-dielectric metasurface based on nanoholes cuboid arrays is proposed.•The high Q factor metasurface excites toroidal dipole response.•Two Fano resonances are excited based on bound states in the continuum.•Two Fano resonances arise simultaneously at communication wavebands, 1310 nm and 1550 nm.•The metasurface can serve as refractive index sensors and nano lasers. High Q factor multiple Fano resonance excitation in all-dielectric metasurfaces has become an effective mode to design high performance optical devices. This paper proposed an all-dielectric metasurface, composed of silicon cuboid etched with two semicircular holes into a unit cell and periodically arranged on a silica substrate. Numerical results show that triple high Q factor Fano resonances, corresponding to 1310 nm, 1401 nm and 1550 nm, are excited simultaneously, in its transmission spectrum. Toroidal dipole (TD) response can be identified for the resonance at 1310 nm, showing the Q value as high as 2617. By introducing a symmetry breaking, the quasi- bound states in the continuum (BIC) resonances at 1401 nm and 1550 nm are excited, which can be classified by electric quadrupole (EQ) and magnetic dipole (MD) response, respectively. Simulation results demonstrate that by adjusting the structure parameters, the designed metasurface can be tunable to meet the requirements of different applications in near infrared region. The sensing performances of the proposed structure are investigated as well, yielding the refractive index sensitivity of ~ 300 nm/RIU and maximum figure of merit (FOM) of ~ 440. Typical characteristics of the novel structure allow it to cater for the designs and applications of lasers, multiple channel nano sensors and other photonics modules in photonic integrated circuits (PIC) or optical communication devices.